476OA phase I study to evaluate safety and efficacy of BPI-7711 in EGFRm+/T790M+ advanced or recurrent NSCLC patients. (24th November 2019) - Shi, Y; Fang, J; Shu, Y; Wang, D; Yu, H; Zhao, Y; Zhang, L; Zhu, B; Li, X; Chen, G; Shi, J; Zheng, R; et al.
Abstract: Background: BPI-7711 is a 3rd generation irreversible EGFR-TKI that is selectively against EGFR TKI–sensitizing and T790M resistance mutations. A phase I study is conducted to determine the safety and efficacy of BPI-7711 in patients with advanced or recurrent EGFRm+/T790M+ non-small cell lung cancer (NSCLC). Methods: NSCLC patients who had documented disease progression after 1st/2nd generation EGFR-TKI treatment and with EGFRm+/T790M+ confirmed by central lab were enrolled in this multicenter trial (NCT03386955) into "3 + 3" dose escalation or expansion cohorts. BPI-7711 was orally administered at doses of 30∼300 mg in capsules. Treatment efficacy per RECIST 1.1 was evaluated every 6 weeks from the start of daily treatment. The brain metastases (BM) efficacy was assessed based on radiographical response criteria of Response Assessment in Neuro-Oncology Brain Metastases. Results: As of 15 April 2019, 119 patients were enrolled into 6 dose escalation (30mg∼300mg) and 5 dose expansion (30∼240mg) cohorts. BM was present in 44.5% of patients. No DLT was observed and MTD was not reached. For all safety-evaluable patients, the most common treatment related treatment emergent adverse events (TEAEs) (≥10%) were decreases in neutrophil count (17.6%), white blood cell count (17.6%), platelet count (10.1%), and leukopenia (11.8%). Grade ≥3 TEAEs occurred in 16.0% of patients and 8.4% were considered by investigators to be treatment-related. SAEs were reported in 8.4% of patients, and 1.7% were treatment-related. For all efficacy-evaluable patients, the overall ORR of all cohorts was 61.0% and DCR was 89.0%, per independent radiological review committee review. And in 180 mg cohort, the overall ORR was 68.1% and DCR was 95.7%. The ORR for BM was 38.8% across all doses and 45.8% in 180 mg cohort, and DCR for BM was 98.0% and 100% for overall and 180 mg groups. The median progression-free survival was 9.92 months (not mature). Conclusions: BPI-7711 achieved a high overall ORR and promising BM efficacy in NSCLC patients. The safety profile and antitumor activity support continued development of BPI-7711. Phase 2 studies are under preparation. Legal entity responsible for the study: Beta Pharma. Funding: Beta Pharma. Disclosure: M. Greco: Full / Part-time employment: Beta Pharma. G. Hu: Full / Part-time employment: Beta Pharma. X. Li: Full / Part-time employment: Beta Pharma. All other authors have declared no conflicts of interest.